2015
DOI: 10.4103/2229-5070.145587
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Leishmania species by kinetoplast DNA-polymerase chain reaction for the first time in Khaf district, Khorasan-e-Razavi province, Iran

Abstract: Context:Cutaneous leishmaniasis (CL) is an endemic parasitic skin disease in many parts of Iran including Khorasan province. Both clinical forms of the disease, anthroponotic cutaneous leishmaniasis (ACL) and zoonotic cutaneous leishmaniasis (ZCL) are present in this province. However, leishmaniasis molecular map is determined in four cities of Khorasan, but several foci still are remained unknown.Aim:The aim was to identify the species of Leishmania causing CL in Khaf, a District in Khorasan-e-Razavi province… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…The groups were compared using one-way ANOVA test, followed by Tukey's honest significant difference (HSD) test at P value below 0.05. The Microsoft Excel software (Microsoft Inc.) was used to determine the lethal (1) Mortality rate :…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The groups were compared using one-way ANOVA test, followed by Tukey's honest significant difference (HSD) test at P value below 0.05. The Microsoft Excel software (Microsoft Inc.) was used to determine the lethal (1) Mortality rate :…”
Section: Discussionmentioning
confidence: 99%
“…At each interval (6,24,48, and 72 hours), 10 µL of each sample was gently mixed with 10 µL of 0.4% trypan blue on a glass slide. The mortality of parasites was determined by counting the number of alive (not stained) and dead (stained) promastigotes according to the following formula (1). Accordingly, at least 50 microscopic fields were examined for each sample.…”
Section: Experimentationmentioning
confidence: 99%
See 1 more Smart Citation
“…[4161721] Therefore, it is an ideal target for the identification of Leishmania species. [22] Hence, we used kDNA-PCR to determine the genetic diversity of this protozoon, in Ilam Province.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the 45 isolates of Leishmania from different geographical areas of Iran were suspected of cutaneous leishmaniasis (4). Every year it was reported that at least 20 000 cases of cutaneous leishmaniasis are in Iran (5).…”
Section: Introductionmentioning
confidence: 99%